(untitled) (LINGUISTIK TERAPAN, 2020)
In accordance with translation, the metaphors must be translated very carefully in order to avoid misunderstanding. Larson (1984:250) states that If metaphors from source language are translated literally into the target language, they will often be completely misunderstood. Because the translation cannot simply reproduce, or be, the original. In fact, in the folklores there are still literally in translating the text. The aims of this study were to describe the realization of translation strategies in the translation live metaphors in the Sumatera Folklores. The research was conducted by using qualitative design. The data of this study were live metaphors in the Sumatera Folklores. The source of data were 15 folklores in Sumatera. The data were collected through documentary technique and the instrument for collecting the data was documentary sheet. The technique of data analysis was descriptive. The findings of this study revealed that the realization of translation strategies in live metaphors in the Sumatera Folklores into English by applying two process, namely: Single Strategy (91.83%), Double Strategies (8.16%). Metaphors often become the problem in translation and in accordance with translation, the metaphors must be translated from source language (SL) into target language (TL) in order to avoid misunderstanding. Keywords: Translation Strategies, Live Metaphor, Sumatera language, Folklores